Artikel Review: Kajian Efektivitas Tanaman Eucalyptus Globulus Untuk Mencegah Komorbid Penyakit COVID-19 - Vriezka Mierza; Nur Komala Fitri; Priscinya Christiana Debora; Saarah Hamidah Asmara Indratno; Tiwi Ambarati (Journal of Pharmaceutical and Sciences, 2023)
Eucalyptus globulus, a plant that produces essential oils by distilling its leaves, has been studied in the context of preventing comorbid diseases of Covid-19. Through literature searches on Google Scholar and Pubmed with the keywords "Eucalyptus Globulus Plants", "Covid-19 Comorbid Diseases", and "Covid-19", several related articles were reviewed. Gas chromatography analysis (GC-MS) was used to characterize the essential oil content extracted from E. globulus. Several studies have shown that Eucalyptus globulus has anti-diabetic properties, as evidenced by its better inhibition of carbohydrate metabolism enzymes than acarbose. Other studies have also shown significant improvement in managing diabetes complications and blood glucose control compared to the synthetic drug glibenclamide. Eucalyptus globulus also has the effect of inhibiting the growth of mycobacteria, including the Mycobacterium tuberculosis strain that causes tuberculosis. Based on this review, it can be concluded that Eucalyptus globulus can be used as an herbal plant to prevent Covid-19 comorbid diseases such as diabetes, tuberculosis, asthma, hepatitis, and diarrhea. The use of Eucalyptus globulus in the treatment of these co-morbidities could provide potential benefits for the prevention and control of Covid-19 disease.